Syntax, Readability and Ideology in Children's Literature - Puurtinen, Tiina (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1998)
AbstractThis article outlines the aims and methodology of a new study in the field of children's literature. The research makes use of a composite corpus representing original English, original Finnish and translated Finnish from English. The initial focus of this investigation is the analysis of nonfinite constructions, taken as a measure of readability of children's books. Ultimately its aim is to infer, through the interpretation of the lexico-grammatical patterns emerging in the corpus, the ideological norms prevailing in the literary systems of English and Finnish children's fiction.